2020
DOI: 10.1186/s13073-020-00807-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and characteristics of high-level tigecycline resistance Tet(X) in Acinetobacter species

Abstract: Background The recent emergence and dissemination of high-level mobile tigecycline resistance Tet(X) challenge the clinical effectiveness of tigecycline, one of the last-resort therapeutic options for complicated infections caused by multidrug-resistant Gram-negative and Gram-positive pathogens. Although tet(X) has been found in various bacterial species, less is known about phylogeographic distribution and phenotypic variance of different genetic variants. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 43 publications
3
77
4
2
Order By: Relevance
“…A number of obstacles must be addressed before such models can be translated into practical tools, including performing clinical validation and providing implementation guidelines. Nevertheless, we are convinced that ASE predictors would perfectly complement existing in silico tools that infer all kinds of information from DNA variation, for example, tools that predict splicing 48 , evolutionary pressure 49 or estimate pathogenicity 35 . Such tools are already an established part of diagnostic variant interpretation 50 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of obstacles must be addressed before such models can be translated into practical tools, including performing clinical validation and providing implementation guidelines. Nevertheless, we are convinced that ASE predictors would perfectly complement existing in silico tools that infer all kinds of information from DNA variation, for example, tools that predict splicing 48 , evolutionary pressure 49 or estimate pathogenicity 35 . Such tools are already an established part of diagnostic variant interpretation 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, however, during the past two years there have been an explosive number of publications showing that the worst-case scenario with the extensive dissemination of tet (X) into pathogenic microbiota is actively taking place, especially in China [ 15 , 16 , 17 , 18 ]. Current epidemiological data indicate that the variants of tet (X), tet (X3)/(X4)/(X5/X6/X14), can be detected in various ecological compartments in China, including humans and animals (mainly pigs, chickens, and ducks) [ 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. According to a recent epidemiological analysis [ 18 ], the highest occurrence of Tet X-producing isolates has been recorded in China—42, followed by Sierra Leone—5, USA—4, Hungary—3, the Americas—1, the Czech Republic—1, France—1, and Japan—1.…”
Section: Present Situation With Tet (X)mentioning
confidence: 99%
“…Previous phylogenetic analyses suggested that the FMO-encoding genes from the group of environmental bacteria belonging to the Flavobacteriaceae family are most likely to be the origin of the tet (X) genes [ 18 , 19 ]. Indeed, the vast diversity of genes encoding tetracycline-inactivating monooxygenases resides within the species belonging to the Cytophaga, Fusobacterium, and Bacteroides (CFB) group bacteria (alternative naming—Bacteroidetes phylum, consisting of Bacteroidia, Flavobacteriia and Sphingobacteriia classes) ( Figure 1 and Figure 2 ).…”
Section: Phylogeny Of Tet (X) Genesmentioning
confidence: 99%
See 2 more Smart Citations